Chloride-Induced Corrosion Effects on the Structural Performance of Concrete with Rebar and Fibres: A Review - Petar Bajić; Bruno Leporace-Guimil; Carmen Andrade; Nikola Tošić; Albert de la Fuente (Applied Sciences)
Chloride-induced corrosion is a major contributor in the degradation of standardised steel-based products (e.g., rebars and fibres) commonly used for reinforcing concrete structures. Since cracked reinforced concrete elements are determined to be more susceptible to corrosion on the one hand, and fibres are effective in arresting crack growth and improving the post-cracking mechanical behaviour on the other hand, the use of fibres emerges as a promising strategy to enhance durability. This review is focused on the degradation of the load-bearing capacity, caused by chloride corrosion, in concrete elements reinforced with fibres and conventional rebar. Based on the recorded values of ultimate loads and the corresponding deflections in the reviewed studies, a lower decrease in the load-bearing capacity and less severe degradation of ductility were observed in elements where fibres (either steel or macro-synthetic) were used in combination with rebar compared with elements where only rebar was used. Furthermore, the recorded values of corrosion potential (Ecorr), corrosion current density (icorr) and gravimetric measurements indicated lower corrosion damage, delayed corrosion initiation and a prolonged propagation phase of corrosion. However, due to many differences in the methodology among the reviewed studies, the optimal fibre type or quantity cannot be identified unless more studies are performed.